PERDAGANGAN PEREMPUAN INDONESIA DALAM SITUS PENGANTIN PESANAN: PERSPEKTIF FEMINISME SOSIALIS - Husnah, Wabilia (UI Scholars Hub, 2023)
Mail-order bride websites can be easily found in cyberspace. These websites sell Indonesian women to Chinese men as wives. This study aims to explore the phenomenon of women cyber-trafficking in mail-order bride websites, especially the background of mail-order bride websites and their impacts on the victims. This qualitative research used the case study approach and the socialist feminism theory to investigate three mail-order bride websites. This study concludes that the oppression of women on mail-order bride websites is caused by long-standing patriarchy in Indonesia and China reflected in daily practices, cultural manifestations, and literary works in both countries. Capitalism has also played a role in the emergence of mail-order bride websites. This paper suggests promotion of gender equality and eradication of human trafficking in order to minimize cyber-trafficking through mail-order bride websites.